Smartphone Usage and Parent Role Correlated with Risky Dating Behaviour in Adolescent - Irwina Angelia Silvanasari; Florentina Sustini; Eka Mishbahatul Mar'ah Has (Universitas Triatma Mulya, 2018)
Introduction. Dating behavior becomes one of risky behavior in adolescence. The research purpose was to analyze the correlation between smartphone usage and parents role with risky adolescent dating behaviour. Methods. The research design was observational analytic with cross sectional approach. This research was conducted in January 2018. The population was the entire students of class X and XI in Jember X Senior High School. As many as 150 respondents taken with simple random sampling. The independent variables were information seeking, entertainment seeking, use of problematic smartphone, and parents role. The dependent variable was adolescent dating behaviour. Data collection used questionnaire. The data results were analyzed using chi-square and logistic regression (α = 0,05). Results. The research results showed that adolescents with information seeking 5-6 times/day (OR = 7,010; 95% CI = 2,072 - 23,710) and information seeking 2-4 times/day (OR = 4,853; 95% CI = 2,013 - 11,696) tend to have risky dating behavior than adolescents with information seeking > 6 times/day. Adolescents with entertainment seeking > 6 times/day (OR=2,497; 95% CI=1,007-6,190) tend to have risky dating behavior compared to adolescents with entertainment seeking ≤ 4 times/day. Adolescents with poor parent role (OR=2,913; 95% CI=1,294 - 6,554) tend to have risky dating behavior compared to adolescents with good parent role. Conclusion. Wise smartphone usage should be done by adolescent. Parents should be able to open discussion about sexual health and monitor smartphone usage in adolescent. School nurses should be able to provide education related to wise smartphone usage to adolescent.